Hildebrandslied als frühstes Denkmal im deutschsprachigen Raum - Asim Attia (Beni-Suef University International Journal of Humanities and Social Sciences, 2019)
“Hildbrandslied” is a literary model from the Germanic era and is considered as a clear testimony for an existence of a rich literature through this historical period. This work shows the anarchistic atmosphere where the Germanic society lived in, that society loved invasion, fight and gaining more lands. The scarcity of researches in this topic was my passion to start my research which is discussing the conflict between a father and his son who met on the border. When the father tried to convince his son that he is his father but his son insisted on not convincing and accused his father with cowardice. This action led this father to kill his son which declared that instinct of invasion and fight can defeat blood’s consanguinity.